Microstructure characterization and wear performance of WC-10Co/Ti-6Al-4V coating fabricated via electron beam cladding - Chen, Yawei; Wang, De; Wang, Wenqin; Liu, Yong; Sato, Yutaka S.; Yamaguchi, Tomiko; Chen, Yunxia; Wang, Chenghai (Surface & coatings technology, 2021)
In this study, WC-10Co/Ti-6Al-4V coatings were fabricated under varying cladding voltages via electron beam cladding technology. The microstructure, microhardness, and wear performance of the composite coatings were studied. In addition, temperature field simulations were performed for the cladding process applying ABAQUS. The thickness of the coatings ranged from 350 to 850 μm. The presence of α-Ti, (Ti, W)C1-X, and small amounts of WC, TiC, (W, Ti)C1-X, W2C, and β-Ti in the coatings was confirmed. WC and TiC were partially dissolved and, in accordance with the simulated temperature field, resulted in the appearance of (W, Ti)C1-X around the WC particles. Moreover, the consumption of C atoms was beneficial for the diffusion of W atoms into the TiC lattice to form (Ti, W)C1-X. In the comparison of experimental and numerical simulation results, it was found that a deeper penetration and further settlement of WC particles was observed experimentally, when a higher cladding voltage was applied. The coating prepared under 65 kV exhibited the best mechanical performance and its friction mechanism entailed abrasive and adhesive wear. •WC-10Co/Ti-6Al-4V composite coatings were fabricated via electron beam cladding.•Microstructures of the coatings were characterized.•Formation mechanisms of (Ti, W)C1-X and (W, Ti)C1-X were investigated.•The coating fabricated at 65 kV exhibited best wear resistance performance.